Perspectivas de idosos sobre acesso e acolhimento em unidades de pronto atendimento - Scolari-Francisco, Giovana Aparecida de Souza (2016)
By considering that old age is coupled with a high number of chronic conditions and that the frequent intensification of these conditions boosts the demand for emergency services, particularly in the Emergency Care Units, it becomes necessary that the access and welcoming devices are held with commitment, in order to provide assistance to this share of the population with accountability for the care. Accordingly, this study was intended to analyze the access and the welcoming practices towards the elderly people in Emergency Care Units. It was a descriptive and exploratory study, with a qualitative approach, which was conducted with elderly people and their relatives who were served in the two Emergency Care Units in a city located in the countryside of Paraná, Brazil. Data were collected between December 2015 and April 2016, guided by semi-structured interviews. Data analysis was performed by means of the open and axial coding steps of the analytical technique of Grounded Theory. The results showed the strengths and weaknesses with regard to the access of elderly people in these services. Among the strengths, one can highlight the guarantee of care and the access to greater resources, such as exams and medicines. Concerning the weaknesses, there were reports about the distance from the health facility, with the need to use public transport, the indiscriminate search, including because of non-urgent causes, which entail work overload, delay in the time of care and inability to solve the health needs of the population. It was made clear that the welcoming is perceived among the practices of receptivity at the time of entering the service, during the continuity of care, provided by the work dynamics, and also in the aspects relating to ambience and infrastructure. Although most of the elderly people feel satisfied, some difficulties were indicated in the welcoming process, such as the waiting time for accomplishing exams and obtaining their results. It is concluded that there is a need to restructure the assistance provided, based on the consolidation of public policies, with the aim of providing care with respect to the specific features of the elderly population. The results of this study provide subsidies for the discussion about the care of elderly people in emergency situations and for the planning of adjustments in the organization of work in Emergency Care Units, thereby collaborating with the improvement of health care of the elderly person.